300IR 5-Grass Pollen Sublingual Tablet Offers Relief from Nasal Symptoms in Patients with Allergic Rhinitis. Issue 6 (November 2014) - Serrano, Elie; Wahn, Hans Ulrich; Didier, Alain; Bachert, Claus
Background: 300IR 5-grass pollen sublingual immunotherapy tablets have been approved for the treatment of allergic rhinitis (AR) with or without conjunctivitis in adults and children >5 years with grass pollen allergy. This study was designed to review data on nasal symptoms with 300IR 5-grass pollen sublingual tablets in adults and children. Methods: We reviewed data from four double-blind, placebo-controlled, randomized clinical trials. Two groups of patients who received a daily dose of either placebo or 300IR 5-grass pollen sublingual tablets starting 4 months before the expected start of the pollen season and continuing through the season were compared (analysis of covariance) for scores of sneezing, rhinorrhea, nasal pruritus, nasal congestion, total nasal symptom score (TNSS), and adult Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ) scores. Results: Data for 266 children (one pediatric trial) and 1036 adults (three trials) were analyzed. Compared with the placebo groups, mean TNSS in the 300IR groups was lower by 22% in children and 19–36% in adults. Among the four nasal symptoms, the lowest scores relative to placebo were for nasal congestion in children (31%) and adults (43%). Mean adult RQLQ scores were 21–31% lower in the 300IR group than in the placebo group. Conclusion: Allergen immunotherapy with 300IR 5-grass pollen sublingual tablets was consistently associated with AR symptom relief in adults and children and provided a clinically meaningful improvement in quality of life.